Subspace Selection via DR-Submodular Maximization on Lattices - Nakashima, So; Maehara, Takanori (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
The subspace selection problem seeks a subspace that maximizes an objective function under some constraint. This problem includes several important machine learning problems such as the principal component analysis and sparse dictionary selection problem. Often, these problems can be (exactly or approximately) solved using greedy algorithms. Here, we are interested in why these problems can be solved by greedy algorithms, and what classes of objective functions and constraints admit this property. In this study, we focus on the fact that the set of subspaces forms a lattice, then formulate the problems as optimization problems on lattices. Then, we introduce a new class of functions on lattices, directional DR-submodular functions, to characterize the approximability of problems. We prove that the principal component analysis, sparse dictionary selection problem, and these generalizations are monotone directional DRsubmodularity functions. We also prove the “quantum version” of the cut function is a non-monotone directional DR submodular function. Using these results, we propose new solvable feature selection problems (generalized principal component analysis and quantum maximum cut problem), and improve the approximation ratio of the sparse dictionary selection problem in certain instances. We show that, under several constraints, the directional DRsubmodular function maximization problem can be solved efficiently with provable approximation factors.